Предмет: Алгебра, автор: Галя23

Упростить 4 sin(3П/2-a)*cos(П2+a)*сos(П+2a)

Ответы

Автор ответа: dtnth
0

4sin (frac{3}{2}*pi-a)*cos(frac{pi}{2}+a)*cos(pi+2a)=4*(-cos a)*(-sin a)*(-cos (2a))=-2*2sina cos a* cos(2a)=-2*sin(2a)cos(2a)=-sin(2*2a)=-sin(4a)

Автор ответа: Аноним
0

4 sin(3П/2-a)*cos(П2+a)*сos(П+2a)= -4cosa * (- sina ) * (-cos2a) = - 4cosa *  sina  * cos2a =

-2 * (2cosa *  sina )  * cos2a =-2 sin 2a * cos2a= - sin4a

Похожие вопросы
Предмет: Алгебра, автор: daniilnosik5
Предмет: Химия, автор: tsilaeva767